PERANCANGAN SISTEM INFORMASI MAGANG BERBASIS WEB RESPONSIVE MENGGUNAKAN GRID SYSTEM DAN CSS MEDIA QUERY UNTUK PT. PERUMDAM TIRTA DARMA AYU (Current Research in Education: Conference Series Journal, 2023)
The efforts of the Regional Drinking Water Company (PERUMDA Tirta Darma Ayu) of Indramayu Regency in improving the quality of human resources, one of which is by holding internship activities. Internship data processing which is currently running is still done using document forms, information related to internships is still difficult to obtain. This allows the risk of data inaccuracy and information uncertainty. The purpose of this research is to provide a responsive web-based internship information system design using the Grid System and CSS Media Query so that it can be accessed by users on various devices such as laptops, smartphones or tablets, the web display automatically changes to accommodate the display according to the resolution, size image, and scripting capabilities. The method used is Research and Development (RD) to produce an appropriate information system. The results of this research are flowcharts, system designs, prototypes and responsive web interfaces using the Grid System and CSS Media Query. The conclusion of this research is that the design made can be used as an illustration to design a responsive web information system that can be accessed by the latest devices and can assist in processing internship data.